Copper-Catalyzed Semihydrogenation of Alkynes to Z-Alkenes - Semba, Kazuhiko; Kameyama, Ryohei; Nakao, Yoshiaki (Synlett, 2015)
Copper-catalyzed semihydrogenation of internal alkynes has been developed. The reaction proceeds under an atmosphere of hydrogen (5 atm) at 100 °C in the presence of a readily available [(PPh3)CuCl]4 catalyst to give various Z-alkenes stereoselectively.
Keywords: alkynes; alkenes; catalysis; copper; hydrogenation